Analysis of changes in biochemical parameters of oral liquid under the influence of lecithin-calcium complex in young patients with multiple caries - Volkova, O. S. (Zaporozhye Medical Journal, 2018)
Given the high prevalence of dental caries, it is important to find new means and methods of prevention. At present preparations of natural origin, such as lecithin and calcium citrate, are widely used. The aim was to study the lecithin-calcium complex effect on the oral fluid biochemical parameters of individuals with multiple dental caries. Materials and methods. 85 KhNMU Dental Faculty students-volunteers were examined. Groups of participants were formed depending on the dental caries intensity level index value for the oral fluid biochemical parameters determination (degree of oral dysbiosis, antioxidant-prooxidant index) in patients before and after the start of the lecithin-calcium complex treatment course. Results. In persons with multiple dental caries the degree of dysbiosis is 3 times higher than normal, the concentration of calcium decreases by 1.5 times and the antioxidant-prooxidant index reduces by 2 times. After lecithin-calcium complex treatment course the dysbiosis degree decreases almost by 8 times, the concentration of calcium and API return to normal. This indicates the ability of the lecithin-calcium complex to regulate the oral cavity microbiocenosis and restore antioxidant-prooxidant indices. Conclusions. In patients with multiple dental caries the phenomena of the oral cavity dysbiosis, a decrease in the protective antioxidant system level and a decrease in the oral fluid calcium concentration are observed. The lecithin-calcium complex intake during the month completely eliminated the phenomenon of dysbiosis in the oral cavity, increased the antioxidant-prooxidant system level and the oral fluid calcium concentration to normal.